Life-courses, social change and politics: Evidence for the role of politically motivated structural-level influences on individual criminal careers - Farrall, Stephen (Criminology & criminal justice, 2025)
Criminal careers research is one of the largest fields of research in modern criminology. However, it has almost exclusively focussed on individual-level explanations of onset, maintenance and desistance. In this article, and in part inspired by recent work by John Braithwaite (and others), we argue that criminal careers research needs to attend in greater detail to the macro-logical processes which shape offending careers. Herein, we outline key conceptual elements, which, when incorporated with life-course theorising, may offer a way to include specific social, economic, cultural, historical, and political influences on criminal careers. Our aim is to examine a key knowledge gap within developmental and life-course criminology (namely, the role of politically motivated policy choices) and to propose a possible solution to this. In so doing, we summarise our recent research exploring the role of political processes on criminal careers using birth cohort data. We highlight the need for life-course and developmental criminology to explore the detailed role of structural-level processes in the explanation of individual-level offending careers. As such, our article presents new directions for examination and empirical research.